Aset Biologis dan Kinerja Keuangan Perusahaan Agrikultur (Studi pada Bursa Efek Indonesia) - Maharani, Dewi; Falikhatun, Falikhatun (Kompartemen : Jurnal Ilmiah Akuntansi, 2019)
Agricultural firm is one of the companies that provide great contribution on income of Indonesia. Agricultural sector has different characteristics from other sectors, namely agricultural activity. Agricultural activity based on PSAK No. 69 is a biological transformation process which is the development of a biological asset that requires precise measurement. PSAK No. 69 requires the company to measure fair value. Fair value measurement of the effect on the financial performance of the company due to volatility will ensue. Describes the default risk of volatility from financial statements. Improving the performance of companies to attract investors in the company’s shares on implanting. This research aims to examine the relationship between the intensity of the biological assets, the size of the company, the company’s growth rate, and leverage financial performance with agricultural firm listed on the Indonesia stock exchange from year 2009 until 2016. This study uses a quantitative approach with descriptive data analysis using classical assumptions and hypothesis testing with multiple linear regression analysis. The results of this study found that the intensity of the biological assets, the growth rate of the company, as well as the leveraged effect significantly to the company’s financial performance. Keywords: Biological Assets, Historical Value, Fair Value, Financial Performance.